2010
DOI: 10.1161/circresaha.109.212530
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα2 Deletion Causes Aberrant Expression and Activation of NAD(P)H Oxidase and Consequent Endothelial Dysfunction In Vivo

Abstract: A MP-activated protein kinase (AMPK) is a serine/threonine kinase consisting of ␣, ␤, and ␥ subunits, each of which has at least 2 isoforms. The ␣ subunit possesses catalytic activity, whereas the ␤ and ␥ regulatory subunits maintain the stability of the heterotrimer complex. AMPK phosphorylates multiple targets, in vivo and in vitro. These targets include several biosynthetic enzymes such as acetylCoA carboxylase, hydroxymethylglutaryl-CoA reductase, and glycogen synthase. The importance of AMPK␣ is illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
268
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 286 publications
(288 citation statements)
references
References 39 publications
16
268
0
4
Order By: Relevance
“…The AMPK signaling pathway is important in maintaining cellular survival during stress by regulating metabolic homeostasis (48). Consistent with the present findings, previous studies have suggested that the activation of the AMPK pathway suppresses the function of the NF-κB pathway (49)(50)(51)(52)(53)(54). AMPK has certain direct phosphorylation targets (55); however, it is possible that AMPK inhibits NF-κB signaling through its downstream effectors, including peroxisome proliferator-activated receptor γ co-activator 1α and sirtuin (silent mating type information regulation 2 homolog) 1, which suppress inflammatory factors.…”
Section: Discussionsupporting
confidence: 91%
“…The AMPK signaling pathway is important in maintaining cellular survival during stress by regulating metabolic homeostasis (48). Consistent with the present findings, previous studies have suggested that the activation of the AMPK pathway suppresses the function of the NF-κB pathway (49)(50)(51)(52)(53)(54). AMPK has certain direct phosphorylation targets (55); however, it is possible that AMPK inhibits NF-κB signaling through its downstream effectors, including peroxisome proliferator-activated receptor γ co-activator 1α and sirtuin (silent mating type information regulation 2 homolog) 1, which suppress inflammatory factors.…”
Section: Discussionsupporting
confidence: 91%
“…These results strongly suggest that ROS-LKB1 might be required for AMPK activation by probucol in glioma cells. Studies [21,28] have demonstrated antioxidant effects of probucol and AMPK in vivo. This apparently contradictory observation might be similar to ischemic preconditioning by ROS, in which low levels of ROS precondition the tissues to prevent the massive production of reactive species in index hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA (400 ng) from each sample was used for cDNA synthesis using the iScript cDNA synthesis kit (Bio-Rad Laboratories, Hercules, CA, USA) according to the manufacturer's instructions and as described previously [21] . Prepared cDNA samples were amplified and analyzed with PCR using the following primers: p27 Kip1 , 5'-CGCTTTTGTTC-GGTTTTGTT-3' (forward) and 5'-TTCGGAGCTGTTTAC-GTCTG-3' (reverse).…”
Section: Semi-quantitative Reverse Transcription Polymerase Chain Reamentioning
confidence: 99%
“…6, B, C, and F). Wang et al reported that deletion of AMPK␣2 results in the constitutive activation of NF-B in mouse aortic endothelial cells (47). In addition, many studies have reported that the activation of AMPK inhibits the NF-B pathway (48 -51).…”
Section: Discussionmentioning
confidence: 99%